Case Study of The Teaching and Learning English for Junior High School Students - Ike Anisa (Faculty of Language and Literature, University of Surakarta, 2019)
This study has an aim to describe the teaching learning process by the teacher and the students in junior high school. The researcher wants to describe about the teaching learning process and the factors dealing with the problems on how the process of teaching and learning English for the junior high school students. The researcher chooses the class eight of junior high school students in SMP AL-Islam Kartasura as the source. The other source is taken from the teachers of SMP Al-Islam Kartasura. The data are collected then analyzed by descriptive qualitative method. From the result, it can be concluded that the teaching learning process on the class eight students of the junior high school of SMP Al-Islam Kartasura is as follows; preparation, teaching learning process, material, media, teacher role, students role, obstacles and the solutions.